Geografii teatrale pe firul istoriei și al râului IV – Cu Caragiale în unda timpului - Stamatoiu, Cristian (Theatrical Research, 2023)
Theatrical Geographies on the Thread of History and the River IV – With Caragiale in the Wave of Time “Theatrical Geographies Alongside the History and the River (IV): With Caragiale on the Waves of the Times“ is a study about the relation between the Times and the works of the Romanian classic of the drama, I.L. Caragiale. He created in the Balkan context of the “La Belle Époque“, with some historical events from this era being reflected in his satirical work, to the point of being tragic. Simultaneously, there are investigated the moments of his dramatic premieres and the narratives patterns between the “incipt” and the “finis” of his literary plots and even beyond their conclusions.